Students’ and Teachers' Perceptions on the Implementation of Skimming and Scanning Techniques for Reading Comprehension - Khaeriyah, Nurul Khalizah; Sunra, La; Baa, Sultan (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study aims to explore students’ and teachers’ points of view on the implementation of skimming and scanning techniques for reading comprehension. This research used qualitative methods and the instrument used in collecting the data was an interview. The population of this research was the 12th grade of the students SMKN 3 Gowa academic year 2022/2023. The participants of the interview were 6 students and the English teachers. The result of data analysis showed that both students’ and teachers’ perceptions generally hold positive views towards skimming and scanning techniques as effective strategies for reading comprehension. Skimming was perceived as beneficial for quickly grasping the main idea of a text, while scanning was valued for efficiently locating specific information. Participants acknowledged the importance of these techniques in academic contexts and daily life. However, challenges were identified, including difficulties in applying skimming and scanning accurately, especially for complex texts. Students expressed a need for more guided practice and explicit instruction to improve their proficiency in these skills. Overall, the study underscores the significance of incorporating skimming and scanning techniques effectively into reading instruction. By addressing the identified challenges and providing targeted support, educators can enhance students' reading comprehension skills and empower them to navigate various texts with confidence.